Growth and Yield Performance of Peanut (Arachis hypogaea) Lines in Pampanga, Philippines - Gatan, Mary Grace (JPAIR Multidisciplinary Research, 2015)
Peanut (Arachis hypogaea Linn) is grown on nearly 23.95 million hectares worldwide with a total production of 36.45 million tons. In the country, peanut is one of the food legumes with commercial importance that contributed much to domestic earnings. There are promising peanut lines that need to be evaluated to pass the National Seed Industry Council (NSIC) Certification. Hence, the National Cooperative Trials from 2011-2014 were conducted to evaluate their agronomic characteristics, reaction to diseases and yield potential in Pampanga, Philippines. Experimental trials were laid out following Randomized Complete Block Design (RCBD). Data were subjected to Analysis of Variance (ANOVA) and treatment means were compared using Least Significant Difference (LSD). At wet season trials, results revealed significant differences in all treatments relative to days to flower, number of pods/plant, weight of 100 seeds, shelling percentage and pod yield except days to maturity.Â The ICGV 00350 and ICGV 99046 obtained the highest pod yield with 2.1 and of 2.4 tons/ha, respectively. During dry season, significant differences were noted among peanut lines in relation to days to flower, days to maturity, number of pods/ plant, weight of 100 seeds, shelling percentage and pod yield (tons/ha). The ICGV 01273 out yielded the 10 peanut lines. Â Keywordsâ€” Agriculture, National Cooperative Trials, Arachis hypogaea, experimental trials, Philippines, Asia